Analysis of Transformational Leadership In Improving Performance and Organizational Citizenship Behavior (OCB) Employees of Sayap Ibu Foundation, Banten Province - Hamsinah Hamsinah (LPPM-STPI, 2022)
The purpose of this research is to analyze Transformational Leadership in improving employee performance and OCB behavior or Employee Organizational Citizenship Behavior (OCB). This research method is descriptive qualitative in nature, namely research that is intended to understand the phenomena experienced by research subjects and produce descriptive data in the form of written words and the behavior of the people observed.1 This study was carried out in a fundamental, in-depth and process-oriented manner. Descriptive qualitative research is also a form of research that aims to describe existing phenomena, both natural phenomena and man-made phenomena. The phenomena can be in the form of activities, characteristics, changes, similarities, and differences between one phenomenon and another. The initiative attitude of the employees can result in an increase in the performance and productivity of the company/organization. Of course, this is important for the progress of the company so that the impact of employee initiatives is very large for the company/organization. Employees who have qualified abilities do not necessarily have good initiative. This initiative includes providing improvement ideas and improvements. In this study, the authors narrow the point of initiative performance on OCB (Organizational Citizenship Behavior) attitudes.